Evaluating risk in perpetrator narratives: resituating Jonathan Littell's The Kindly Ones as historical fiction. Issue 3 (16th April 2017) - Curthoys, Ned
ABSTRACT: This article considers a surge in critical enthusiasm for Holocaust-themed fictions that manipulate empathetic response to endanger and destabilise a reader used to the reiteration of various pieties about the ineffable horror of those events. It argues that interpretive prisms stimulated by the rise of ethical criticism and the postcolonial turn in Holocaust studies are powerfully suggestive but in danger of privileging the self-problematising experience of reading, so overlooking the pragmatic, functional orientation of historical novels which wish to contribute to an informed conversation about the meaning of the past. It explores Jonathan Littell's The Kindly Ones as an exemplary case study of a critically engaged historical novel. Recent theories of unreliable narrative informed by considerations of rhetorical technique, genre positioning, and character type, can help to illuminate the novel's contribution to the ongoing process of historical understanding.